STUDI TENTANG MAKNA MOTIF (BENTUK, WARNA, DAN PENEMPATAN) PADA TABUIK DI KOTA PARIAMAN - Melati Sukma; Yofita Sandra (Universitas Negeri Padang, 2020)
This study aims to: 1) Describe the meaning of the Tabuik Pariaman motif shape 2) Describe the meaning of the colors in the Tabuik Pariaman motif 3) Describe the meaning of the placement of the motifs in Tabuik Pariaman.This type of research is qualitative using a descriptive approach. The author conducted this research in Pariaman, West Sumatra. Data collection procedures are carried out by 1) observation or going to the field, 2) interviews, and documentation in the form of recordings and photos 3). Data processing, 4) data analysis, 5) conclusion of the results. The conclusions of the study are: 1) The meaning of the shape of the motif in Tabuik Pariaman has a meaning as a rule in the life order of the Minangkabau community that upholds customs and religion. 2) The meaning of color in Tabuik has the meaning of decorations that beautify Tabuik in order to attract the appeal of the community and tourists. 3) Meaning The placement of motifs in Tabuik is a symbol of religion, customs, and life.Kata Kunci: Makna Motif, Bentuk, Warna, Penempatan, Tabuik Pariaman.